2006
DOI: 10.2215/cjn.02271205
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Pilot Trial Comparing Cyclosporine and Azathioprine for Maintenance Therapy in Diffuse Lupus Nephritis over Four Years

Abstract: There is not agreement about the best maintenance treatment for patients with diffuse lupus nephritis. This multicenter, randomized trial compared the safety and efficacy of cyclosporine and azathioprine. Seventy-five patients with diffuse proliferative lupus were given three intravenous methylprednisolone pulses followed by prednisone and oral cyclophosphamide for a median of 90 d. Subsequently, patients were randomly assigned either to cyclosporine or to azathioprine for 2 yr (core study). Treatment continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(74 citation statements)
references
References 20 publications
2
70
0
2
Order By: Relevance
“…12) Recent studies reported low dose cyclosporine therapy, which was adjusted to gain of blood trough concentration approximate 80-150 ng/mL, was an effective and less toxic cyclosporine therapy for the regulation of connective tissue diseases with RA, 13) SLE, [14][15][16] and lupus nephritis. [17][18][19] Population pharmacokinetic methods, with the ability to incorporate covariates from sparse drug concentration data, offer an opportunity to generate a dosing regimen. Although a dosing method that takes into account the various factors that influence the pharmacokinetics of cyclosporine is needed, pharmacokinetic studies on cyclosporine in collagen disease patients are limited, as are population pharmacokinetic studies.…”
mentioning
confidence: 99%
“…12) Recent studies reported low dose cyclosporine therapy, which was adjusted to gain of blood trough concentration approximate 80-150 ng/mL, was an effective and less toxic cyclosporine therapy for the regulation of connective tissue diseases with RA, 13) SLE, [14][15][16] and lupus nephritis. [17][18][19] Population pharmacokinetic methods, with the ability to incorporate covariates from sparse drug concentration data, offer an opportunity to generate a dosing regimen. Although a dosing method that takes into account the various factors that influence the pharmacokinetics of cyclosporine is needed, pharmacokinetic studies on cyclosporine in collagen disease patients are limited, as are population pharmacokinetic studies.…”
mentioning
confidence: 99%
“…Currently available clinical trials propound sequential therapy as an effective and safe alternative for treating severe LN in patients of white, Asian, African, or Hispanic ancestry (18)(19)(20)(21)(22)(23)(24)(25)(26). We have seen a comforting decline in CKD (7% or less) and mortality (10% or less) with the use of sequential therapies in the past two decades.…”
Section: Resultsmentioning
confidence: 99%
“…The risk for CKD from long-term exposure to calcineurin inhibitors is still not known because clinical trials limited the exposure of those drugs to a maximum of 24 months of active therapy. Moroni et al (25) in a maintenance RCT compared cyclosporine (n536) with AZA (n533) for 24 months in predominantly white patients with SLE who had diffuse proliferative LN. Relapses were similar in the two groups (19.4% and 24.2%).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and histologic improvement with cyclosporine has been reported also in proliferative lupus nephritis both when the drug was given in patients resistant to IV cyclophosphamide (14) or when given for maintenance (15). In a randomized, controlled trial of proliferative lupus nephritis, Moroni et al showed equivalence between cyclosporine and azathioprine for maintenance therapy up to four years (16).…”
Section: Cyclosporinementioning
confidence: 95%